Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fcimb.2022.1042070
|View full text |Cite
|
Sign up to set email alerts
|

Current and future perspectives for Helicobacter pylori treatment and management: From antibiotics to probiotics

Abstract: Helicobacter pylori (H. pylori) is a Gram-negative anaerobic bacterium that colonizes the human stomach and is the leading cause of gastric diseases such as chronic gastritis and peptic ulcers, as well as the most definite and controllable risk factor for the development of gastric cancer. Currently, the regimen for H. pylori eradication has changed from triple to quadruple, the course of treatment has been extended, and the type and dose of antibiotics have been adjusted, with limited improvement in efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…H. pylori is a microaerobic organism and susceptible to increased oxygen levels, thus, the delivery of nanoparticles that include oxygen into the gastric mucus layer could render the bacterium vulnerable. In addition, multiple aspects of the interaction of H. pylori with the gastrointestinal microbiome are addressed by current research and will influence future research [360][361][362][363][364] . The exclusive property of H. pylori to colonize and infect the gastric mucosa affects the biodiversity of other gastric bacteria and their role in either enhancing or mitigating H. pylori-induced gastric inflammation; this needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori is a microaerobic organism and susceptible to increased oxygen levels, thus, the delivery of nanoparticles that include oxygen into the gastric mucus layer could render the bacterium vulnerable. In addition, multiple aspects of the interaction of H. pylori with the gastrointestinal microbiome are addressed by current research and will influence future research [360][361][362][363][364] . The exclusive property of H. pylori to colonize and infect the gastric mucosa affects the biodiversity of other gastric bacteria and their role in either enhancing or mitigating H. pylori-induced gastric inflammation; this needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…17 Twelve clinical trials in six countries (Germany, Ireland, Russia, Romania, China, and India) investigating the efficacy and safety of L. reuteri showed improved eradication rates and reduced antibiotic side effects. 18 The eradication rate ranged between 9% and 20%, with the highest rate reported by Parth et al in India. 19 To our knowledge, the efficacy of a Lactobacillus reuteri DSM 17648 probiotic as an adjunct treatment in H. pylori management has yet to be studied in Malaysian and South East Asian cohorts.…”
Section: Introductionmentioning
confidence: 95%
“…Among all 11 randomized controlled trials, five involving Lactobacillus reuteri have shown successful results 17 . Twelve clinical trials in six countries (Germany, Ireland, Russia, Romania, China, and India) investigating the efficacy and safety of L. reuteri showed improved eradication rates and reduced antibiotic side effects 18 . The eradication rate ranged between 9% and 20%, with the highest rate reported by Parth et al in India 19 …”
Section: Introductionmentioning
confidence: 99%
“…With around 50% of the world's population infected, H. pylori is the most widespread infection. 1,2 It is well recognized that H. pylori is the primary cause of chronic gastritis, peptic ulcer, gastric cancer, and gastric mucosaassociated lymphoid tissue (MALT) lymphoma, and is linked to various extra-intestinal disorders. 3,4 Most of the time, bacterial colonization lasts the entirety of a person's life, and it can have a variety of clinical symptoms, ranging from asymptomatic people to those who have serious outcomes.…”
Section: Introductionmentioning
confidence: 99%